Determinants of Broiler Production and its Economic Impact: Panel Data Evidence from Indonesia's Core Provinces - Samuel Alkadri; Ahmad Rodoni; Elmiwati (Greenation Research & Yayasan Global Resarch National, 2025)
The broiler chicken industry is a vital component of Indonesia's agricultural sector, possessing significant potential for economic growth and food security. However, it is constrained by challenges including high capital requirements, price volatility, and structural inefficiencies within its core-plasma partnership model. This study aims to analyze the primary determinants of broiler production and quantify its subsequent impact on regional economic output. Using a balanced panel dataset from 2000 to 2023 across five key provinces in Java—which collectively represent the national production hub—this research employs panel data regression analysis to examine the influence of the number of core farmers, price, bank credit, and domestic investment on broiler production volume. A subsequent model assesses the impact of production on Gross Regional Domestic Product (GRDP). The findings reveal that the number of farmers, bank credit, and domestic investment are significant positive drivers of production. Conversely, price exhibits a significant negative relationship, a counter-intuitive result attributed to structural market failures within the core-plasma system where input costs are controlled by output buyers. Furthermore, the analysis confirms that broiler production has a significant and positive impact on GRDP, underscoring the sector's role as an engine for regional economic growth. The study concludes that unlocking the industry's full potential requires policy interventions focused on reforming partnership models and enhancing access to capital for farmers.